Nagoya Contemporary Art Fair 1993. - Nagoya City Gallery, Nagoya (Nagoya : Nagoya Contemporary Art Fair, 1993)
Leibowitz, Cary S. ; Ito, Fukushi ; Hanazawa, Yota ; Maro, Sumi ; Nishimura, Yohei ; Iwata, Kiyoshi ; Mikami, Seiko ; Shoichi, Ida ; etc.
Nagoya Contemporary Art Fair 1993, Nagoya City Gallery, Nagoya, 20-25 April 1993
boek